2019
DOI: 10.1177/0284185119851235
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between magnetic resonance imaging and the level of tumor-infiltrating lymphocytes in patients with estrogen receptor-negative HER2-positive breast cancer

Abstract: Background High levels of tumor-infiltrating lymphocytes (TILs) are associated with improved prognosis and response to therapy in patients with human epidermal growth factor receptor 2 (HER2)-positive breast cancer. Purpose This study investigated the associations between TIL levels and magnetic resonance imaging (MRI) findings in patients with estrogen receptor (ER)-negative HER-2 positive breast cancer. Material and Methods This study included 110 consecutive patients with surgically confirmed ER-negative HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…3) [37]. Low tumor peak enhancement at MRI indicating less aggressiveness was significantly associated with high TILs (OR, 1.01; p = .020) [38]. These results are consistent with previous studies showing that TILs observed in breast cancers were associated with higher rate of pCR or improved overall survival outcomes [5,6].…”
Section: Luminal Subtypesupporting
confidence: 85%
“…3) [37]. Low tumor peak enhancement at MRI indicating less aggressiveness was significantly associated with high TILs (OR, 1.01; p = .020) [38]. These results are consistent with previous studies showing that TILs observed in breast cancers were associated with higher rate of pCR or improved overall survival outcomes [5,6].…”
Section: Luminal Subtypesupporting
confidence: 85%
“…The contrast enhancement patterns of breast MRI were associated with angiogenesis 34 . Choi et al 32 evaluated the kinetic enhancement pattern and reported that high peak enhancement was significantly associated with low TILs. Among the quantitative parameters of CEUS, the lesions with high TILs had higher PI values, which was known to be linked with more angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…32,35 Interestingly, this is not consistent with our results, as these previous studies excluded the non-mass-like lesions, and as the differences in the size and placement of ROIs may change the ADC values. Ku et al 33 found that persistent kinetic enhancement is associated with a low TIL level in TNBC, and Choi et al 36 reported that high peak enhancement was significantly associated with low TILs in TNBC and HER2-positive breast cancer. These two findings by Ku et al and Choi et al also contrasted the current study, in which no significant difference was observed between TIC curve and TIL levels.…”
Section: Discussionmentioning
confidence: 99%